An evaluation of the water tariff policy: a case study of the Thulamela Local Municipality - Moloto, P. I.; Khalo, T. (International Conference on Public Administration and Development Alternatives (IPADA), 2017)
The main purpose of this paper was to evaluate the water tariff policy in Thulamela Municipality. The study had four objectives to answer the research question which were: To evaluate the effectiveness of water tariffs in Thulamela by examining the three locations of Tswinga, Dididi and Thohoyandou Block K; To determine the effectiveness and acceptability of the water cost recovery policy; To determine the attitudes of the community towards water tariffs and non-payment and to determine the challenges encountered in the provision and supply of water in the Thulamela Municipality. A mixed method approach was used for this study combining structured questionnaires and open ended interviews. This allowed both qualitative and quantitative analyses to be done and to draw out conclusions from the community responding to the survey carried out. The findings of the study have showed that there are different opinions and perspectives on the issue of the water tariff policy. More than 50% of the populace interviewed noted that they do not view tariffs as a burden, unaffordable and unsustainable phenomenon while others found the whole water tariff policy to be a burden, unaffordable and unsustainable. Despite these few hiccups the water tariffs have been widely accepted in rural communities though more need to be done for every household to embrace and acknowledge the need to play their part in the maintenance and repairing of water services. The results also show that the sample households have a strong willingness to pay for water tariffs as indicated by 76% of respondents who agreed to have a strong attitude towards willingness to pay. Communities acknowledged that it is helpful to pay for water as this will aid the municipality in meeting the maintenance and repairing costs of providing the supply of water. In addition, the sampled households exhibited that they had a strong attitude in approving the appropriateness of water tariffs and accuracy of the water billing system. Lastly, it was noted that there are challenges encountered in the provision and supply of water; the unavailability of proper facilities for accessing water services, inability to afford to use the water services, unreliability and inconvenience of services and lack of awareness and knowledge on the need to pay for water.
Journal article, Published in International Conference on Public Administration and Development Alternatives (IPADA), The 2nd Annual Conference on ‛‛ The Independence of African States in the Age of Globalisation”, July 26-28, 2017
Keywords: Water tariff policy; Water resources; Thulamela Municipality; Adequate water supply; Water-supply -- Law and legislation; Water-supply -- South Africa -- Limpopo; Water-supply, Rural -- South Africa -- Limpopo